90 Growth and carcass characteristics of ram, wether, and short-scrotum lambs: year 2 - Schoenian, Susan (J Anim Sci, 2020)
This was the second year of a study comparing the growth and carcass characteristics of (intact) ram, wether, and short-scrotum lambs from a commercial sheep dairy in Maryland. East Friesian x Lacaune lambs were left intact (RAM, n = 21), castrated (WETHER, n = 25), or made short-scrotum (SS, n = 18). All banding of WETHER and SS lambs was done by d 10. When the lambs averaged 65±17 d and 44.5±10.6 lbs., they were transported to the Western Maryland Research & Education Center, where they grazed cool season pastures and were supplemented with grain (3 lb/d) for 107 d, before being harvested to collect carcass data. Data were analyzed using the MIXED procedure of SAS, with statistical significance set at P ≤ 0.05. Fixed effects included sex and birth type; starting weight was included as a covariate. There was an effect of birth type on final BW, ADG, HCW, CCW, and body wall thickness (BWT), favoring twin-born lambs. RAM and SS lambs had heavier final BW (P < 0.0001) and ADG (P < 0.0001) than WETHER lambs. RAM lambs had heavier hot (P < 0.01) and cold carcass (P < 0.005) weights than WETHER lambs; SS lambs were intermediate. Dressing percentage was higher (P < 0.004) for WETHER lambs and similar for RAM and SS lambs. RAM and SS lambs had larger REA than WETHER lambs (P < 0.03), but not when adjusted to a common weight (P < 0.71). WETHER lambs produced the fattest carcasses, as evidenced by greater BF (3.8±0.2 mm) than RAM and SS lambs (2.2±0.2 mm and 2.7±0.2 mm, respectively). Sex did not influence BWT, KPH, or leg conformation score. RAM lambs yielded a higher percentage of BCTRC (49.9±0.2%) than WETHER lambs (49.1±0.2%); SS lambs were intermediate (49.6±0.3%). For the second year in a row, RAM and SS lambs demonstrated superior growth and carcass composition compared to WETHER lambs.